2013
DOI: 10.3999/jscpt.44.389
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Ritodrine Pharmacokinetics between Singleton and Twin Pregnancies

Abstract: Aim : To determine the pharmacokinetics of ritodrine in singleton and twin pregnancies. Methods : We treated 105 pregnant women(with singletons, n=67 ; with twins, n=38)with continuous infusion of ritodrine and then measured steady-state serum ritodrine concentrations using HPLC. Results : Ritodrine clearance(mean±SD)was significantly lower in women who delivered twins than in those who delivered singletons(1.59±0.30 vs. 1.75±0.43 L/h/kg ; p<0.001). Serum ritodrine concentration did not differ significantly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The blood concentration of ritodrine hydrochloride is considered to be positively correlated with the administration rate, and it has also been reported that the maternal ritodrine clearance is not affected by gestational weeks. 6 Therefore, it is interesting whether the administration rate affects fetal movements; however, there were not enough number of records to study. The rate of 50 μg/min administration, which is the minimum rate, accounted for about half of all records in this study; therefore, ritodrine administration might affect the fetal movement even with minimum dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood concentration of ritodrine hydrochloride is considered to be positively correlated with the administration rate, and it has also been reported that the maternal ritodrine clearance is not affected by gestational weeks. 6 Therefore, it is interesting whether the administration rate affects fetal movements; however, there were not enough number of records to study. The rate of 50 μg/min administration, which is the minimum rate, accounted for about half of all records in this study; therefore, ritodrine administration might affect the fetal movement even with minimum dose.…”
Section: Discussionmentioning
confidence: 99%
“…That means that ritodrine concentration levels in blood are important; however, the level cannot be measured in daily clinical settings. The blood concentration of ritodrine hydrochloride is considered to be positively correlated with the administration rate, and it has also been reported that the maternal ritodrine clearance is not affected by gestational weeks 6 . Therefore, it is interesting whether the administration rate affects fetal movements; however, there were not enough number of records to study.…”
Section: Discussionmentioning
confidence: 99%
“…7) In addition, 3 of the 14 mothers enrolled in that study showed a negative correlation with regard to gestational age and the clearance of unchanged ritodrine. 8) Changes in maternal physiology caused by the continuation of twin pregnancy are considered to be one of the reasons.…”
mentioning
confidence: 99%
“…8) And it was shown that twin pregnancy mothers had a significantly lower systemic clearance of ritodrine than singleton pregnancy. 7) Although there are very few reports regarding the metabolism of ritodrine, including that in single pregnancy, the metabolism process consists mainly of conjugation to sulfate and glucuronide. 9) It has been reported that ritodrine conjugates have no pharmacological activity.…”
mentioning
confidence: 99%